Woody plants diversity and type of vegetation in non cultivated plain of Moutourwa, Far-North, Cameroon - Todou, Gilbert; Froumsia, Moksia; Souaré, Konsala; Nnanga, Jeanne Flore (Journal of Agriculture and Environment for International Development (JAEID), 2016)
In order to valorize the wild vegetal resources for the efficient conservation and sustainable use in sahelo-sudanian zone in Cameroon, a study of non cultivated plain of Moutourwa was carry out to assess the floristic richness, the specific diversity and the type of vegetation. The inventory of all trees and shrubs (dbh ? 2.5 cm) and the determination of the vegetation cover were done in five linear transects (20 m × 1000 m). In total, 27 families, 54 genera and 75 species were found. Caesalpinaceae is the most abundant family that relative abundance (pi*100) is 34.41%, the most abundant genus was Piliostigma (pi*100 = 30.66%) and the most represented species was Piliostigma reticulatum (pi*100 = 29.56%; D = 53.6 stems/ha). The Simpson index (E= 0.89), the Shannon index (H= 3.2) and the equitability index of Pielou (J= 0.74) indicated that there were moderate diversity with more or less equitable species. The wild fruits species were numerous (pi*100 = 32.76%; D = 59.7 stems/ha). A. senegalensis is was the most represented (pi*100 = 9.04 ; D = 16.4) followed by Hexalobus monopetalus (pi*100 = 5.16 ; D = 9.4) and Balanites aegyptiaca (pi*100 = 3.69 ; D = 6.7). These results contribute efficaciously to valorize the wild vegetal resources for efficient conservation and sustainable use.Keywords: Woody plants diversity, conservation, sustainable use, sahelo-sudanian, Moutourwa